Pendekatan Holistik dalam Pendidikan: Analisis Multidimensi Biologis, Sosial, Psikologis dan Spriritual - Abdullah Hasyim Zain; Mu’alimin Mu’alimin; Mukaffan Mukaffan (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
iA iholistic iapproach ito ieducation ihas ibecome ia icrucial iissue iin ithe idevelopment iof icontemporary iscience iand ieducation. iThe irapid idevelopment iof imodern ipsychology idemands ia isynthesis iwithin ian iIslamic iepistemological iframework ito iprovide ia imore icontextual iapproach ito iaddressing iacademic iand ipractical ineeds, iparticularly iin ithe ifields iof ieducation, icounseling, iand icharacter idevelopment. iThis iarticle iaims ito iprovide ibroader iinsights iinto ithe ifactors iinfluencing ichildren's ilearning iand idevelopment. iThis istudy iemployed ia iqualitative iliterature ireview. iArticles iwere icollected ithrough iGoogle iScholar iand iPublish ior iPerish iusing ithe ikeywords i"Holistic iApproach iin iEducation" iAND i"Biological iFactors" iAND i"Social iFactors" iAND i"Psychological iFactors" iAND i"Spiritual iFactors." iOf ithe iinitial i50 iarticles iobtained, ithe iscreening iprocess iyielded i7 iarticles ithat imet ithe icriteria iof ipublication iyear i(2020–2025), itopic irelevance, iand iopen iaccess. iThe ireview irevealed ifour ifactors iinfluencing ichildren's ilearning iand idevelopment: ibiological, isocial, ipsychological, iand ispiritual. iThis iliterature isynthesis ihighlights ithe iimportance iof iunderstanding ithese ifour ifactors iinfluencing ichildren's ilearning iand idevelopment ito istrengthen ithe irelevance iof iIslamic ipsychology iin ithe iacademic iand isocial ispheres. iFurther istudies ineed ito ibroaden ithe iscope iof iempirical imethodology iand ideepen ithe idevelopment iof icross-disciplinary iapplicative imodels.